Penetration of propylene glycol into dentine - Cruz, E.V.; Kota, K.; Huque, J.; Iwaku, M.; Hoshino, E.
Aim: This study aimed to evaluate penetration of propylene glycol into root dentine.
Methodology: Safranin O in propylene glycol and in distilled water were introduced into root canals with and without artificial smear layer. Dye diffusion through dentinal tubules was determined spectrophotometrically. The time required for dye to exit through the apical foramen using propylene glycol and distilled water as vehicles was also determined. The extent and areas of dye penetration on the split surfaces of roots were assessed using Adobe Photoshop and NIH Image Software.
Results: Propylene glycol allowed dye to exit faster through the apical foramen. The area and depth of dye penetration with propylene glycol was significantly greater that with distilled water (P<0.0001). Smear layer significantly delayed the penetration dye.
Conclusion: Propylene glycol delivered dye through the root canal system rapidly and more effectively indicating its potential use in delivering intracanal medicaments.
Keywords: Dentine; Diffusion; Intracanal medicaments; Penetration; Propylene glycol